Rancang Bangun Alat Bantu Fiksasi Pemeriksaan Radiografi Shoulder Joint Proyeksi Inferosuperior Axial - Siti Daryati; Okta Firawan Putra Purwa; Dwi Rochmayanti (Poltekkes Kemenkes Semarang, 2016)
Backgroud: Have been done research about making of the design tools fixation on radiographic examination shoulder against the backdrop of the difficulty in positioning the patient to commit abduction. The purpose of the design is to replace the role of the patient's family or resident physician in charge of holding the cassette and the patient's arm in abduction during the examination takes place.Methods: This research is a quantitative with explorative experimental approach. The method used in data collection that is designing the tools, use tools, and test tools function. Test function tools made directly to the patient in the Radiology department of DR.Sardjito Yogyakarta. The results of test functions are analyzed based check list of respondents about the value of work tools.Results: The results of design tools fixation on radiographic examination shoulder joint inferosuperior axial projections in the form of iron under the buffer, the buffer on iron, steel main buffer, where handrail 1, where handrail 2 and the cassette place. The workings of the device is placed beside the examination table, abduction of the patient's arm and place it on a hand grip and place cassette on a the cassette place. The function test results on the assessment tool's ability to adjust to the state of the patient's arm, the ability of the tool settings when adjusting the tool height to the height of the examination table or brangkar, the ability of the tool settings when adjusting the length of the tool with the patient's arm length of, the ability of the tool setting in place the cassette on tools, the ability of setting tool in positioning the tape on the object of examination, the ability of the tool to produce radiographs that do not cause artifacts..Conclusion: the ability to show the joints between the glenoid cavity of the humeral head to 2.37. It can be concluded that the tools fixation radiographic examination of shoulder joint inferosuperior axial projection has a pretty good performance.